Effectiveness of Combining Learning Analytics and Self-Regulated Learning to Improving Students' Mathematics Performance - Erdyna Dwi Etika; Vera Septi Andrini; Suharto (Proceeding International Conference on Digital Education and Social Science, 2024)
Academic success in mathematics remains a major issue for many students in higher education. The quality of mathematics education can be raised by implementing self-regulated learning (SRL) and analytical learning (LA). This study aims to determine the effect of applying learning analysis and self-regulated learning in improving students' mathematics performance. In this research, quantitative techniques were applied. An experimental design comprising pre- and post-tests was used to carry out this study. Using stratified random sampling, a sample of 120 Mathematics Education students was chosen for this study. An independent t-test was employed in the data analysis procedure to ascertain the disparity in scores between the experimental and control groups. Pre-test scores and Covariance Analysis (ANCOVA) were used to control for differences in initial abilities between groups. The implementation of LA and SRL had a favourable and significant impact on students' mathematical performance, as demonstrated by the results of multiple linear regression analysis, with a rise of 62.37%. With a correlation of 0.0001, the regression coefficients for the LA variable and the SRL variable are 0.5372 and 0.3618, respectively. Comparing the experimental group to the control group, the former had noticeably better metacognitive abilities, problem-solving capabilities, and concept understanding. These results provide a basis for developing more flexible and adaptive higher-level mathematics learning strategies.